Determinants of Customer Satisfaction: A Study of Shoprite Supermarkets in Lagos - Oladeinde WILLIE-DESANYA; David IMHONOPI (Communications of International Proceedings, 2021)
The retail industry in Nigeria, no doubt, has undergone tremendous change over the years as a result of keen competition among the players and customer satisfaction has become such an important factor that can keep a retail store in business if properly managed and can put an end to business when ignored. It is on this premise of the vital role of customer satisfaction to success in the retail industry that this study aimed to critically identify the determinants of customer satisfaction in the retail industry using three selected retail outlets (ShopRite, JustRite and Spar) within Lagos metropolis of Lagos State Nigeria. Accidental sampling was used to select the respondents for this study. 379 copies of questionnaire were obtained from respondents. The Statistical Package for Social Sciences software was used to run the descriptive statistics while Correlation analysis was employed to estimate the relationships between each determinant as independent variable and customer satisfaction as dependent variable. The results from the study revealed that the variable under study product variety, value for money, quality of products and quality of service or customer care are positively significant to customer satisfaction in the retail industry. The study also found out that quality of products and quality of service/customer care were most important to customers followed by value for money and product variety. The researcher recommended that these determinants be considered by retailers and other stakeholders in the retail industry when formulating strategy for customer satisfaction and retention. Further research should explore other factors that influence customer satisfaction.
Keywords: Customer Satisfaction; Retail industry; Customer base; Service delivery; Value for money; product quality and service quality